The demand for multiple currencies: a portfolio approach - Morón, Eduardo A. (1992)
This article looks at the Rolnick and Weber (1982, 1984) theory that maintains that the cause of the US free banking system crisis can be put down to the restrictions on the handing of portfolios imposed on US banks. This hypothesis is backed up by Moron’s (1990) evidence in the case of Peru and, furthermore, by this article which draws up a simple, theoretical outline to illustrate the relevance of this theory. On the basis of the pioneering works by Markowitz (1959) and Klein (1974) the author constructs a free banking model, in which various banks compete with each other, trying to show that their reputation. The reputation factor in this study is considered according to the probability distribution of purchasing power of each particular currency.